MANUFACTURING OF KIVUGUTO MILK AND STABILITY IN STORAGE UNDER REFRIGERATION - Karenzi, Eugene; Fauconnier, Marie-Laure; Destain, Jacqueline; Thonart, Philippe (European Scientific Journal, ESJ, 2015)
The kivugutomilk was processed in a 20 liters bioreactor with three bacteria previously selected in kivuguto traditional milk. The work aimed to study the association of three bacteria previously selected in traditional kivuguto in order to reproduce it in a controlled fermentation, and thereafter to understand its stability during storage under refrigeration. Postacidification, viability, proteolysis, flavor compounds as well as rheological characteristics were monitored for 36 days. The ph decreases from 4.54 to 4.45 and the titratable acidity grew from 73°d to 79°d. The final biomass after storage was 0.60 108 cfu.g-1 which is far higher than the recommended 106 cells.g-1before consumption. The proteolysis was at a range of 3.0 to 7.0 mg.l-1of lysine equivalent, which is too low so that it can’t produce bitter peptides. The evolution of flavor compounds in storage showed that no change found with 3-methylbutan-1-ol, acetic acid and furan-2(5h)-one, whilst pentan-1-ol and furanmethan-2-ol increased slightly upon 24 days’ storage. The complex viscosity decreased from 4 - 5.3 pas before storage to 2.9 - 4.0 pas corresponding respectively to the ratio g''/g' of about 0.3-0.4 with a very low variation. These data allowed the production and the good preservation of kivuguto milk at 4°c on 36 days.